Difficulties encountered in using medicines, medicine related mishaps and selfadopted coping strategies in visually disabled adults - Weeraratne, C.L.; Rosa, C.T.; Opatha, O.K.D.S.T. (University of Colombo, 2011)
Difficulties faced by visually disabled patients in using medicines, self adopted coping strategies and medicine related mishaps are largely unknown. Thus health professionals are poorly prepared to handle medicine related needs of such patients